THE POSSIBLE ROLE OF RENALASE ENZYME IN CARDIOVASCULAR COMPLICATIONS IN CHRONIC KIDNEY DISEASE PATIENTS - Al-shamma, Zainab A A (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this research was to study the possible role of renalase in the controlling blood pressure (BP) in patients with different stages of chronic kidney diseases (CKD) to decrease the incidents of cardiovascular disease in these patients. Methods: The serum levels of renalase were determined by enzyme-linked immune sorbent assay (ELISA) methods in 68 non-diabetic CKD patients in different stages (2–5). Fifty healthy control subjects were included in this study. Renalase high-sensitive C-reactive protein and Cystatin-C were measured by ELISA which is included first incubating the test serum in an antigen-coated polystyrene plate, then enzyme-labeled anti-immunoglobulin is added and the enzyme then remaining in plate after washing provides a measure of the amount of specific antibody in the serum, and in the final step, a substance is added that the enzyme can convert to some detectable signal, most commonly a color change in a chemical substrate. Results: There were a significant difference between serum levels of renalase, in CKD patients stage 5, and CKD patients 2–3 stage than in their healthy control group (p<0.05), in addition to a significant difference in renalase level between CKD stage, 2–3 and stage 5 (p<0.05). There was a significant positive correlation between serum renalase with systolic BP (p<0.05) in CKD patients stage 5. In addition, there was a significant negative correlation between the serum renalase and estimated glomerular filtration rate (p<0.05) in both groups. Conclusions: The main conclusion of the study was the positive significant correlation with systolic BP in CKD patients (stage 5). In addition, the serum renalase levels were elevated according the CKD stage in patients with CKD in different stages (2–5) and it increased with the deterioration of renal function.